2017
DOI: 10.1371/journal.pone.0172941
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of risk factors for diabetes or cardiovascular disease (CVD) is poor among individuals with risk factors for CVD

Abstract: BackgroundThere is limited evidence on whether having pre-existing cardiovascular disease (CVD) or risk factors for CVD such as diabetes, ensures greater knowledge of risk factors important for motivating preventative behaviours. Our objective was to compare knowledge among the Australian public participating in a health check program and their risk status.MethodsData from the Stroke Foundation ‘Know your numbers’ program were used. Staff in community pharmacies provided opportunistic health checks (measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 19 publications
3
24
1
1
Order By: Relevance
“…Intrapersonal barriers, including a lack of knowledge, limited English proficiency, and poor prediagnostic medication adherence, may increase cardiovascular risks and result in delayed hospital presentation and diagnosis at an advanced stage of disease. The participants’ poor knowledge of CHD and risk factors is consistent with recent findings from an Australian study inclusive of many cultures (Kilkenny et al, 2017). Lack of knowledge about CHD is known to undermine appropriate self-management of risk factors among immigrants (de-Graft Aikins, Pitchforth, Allotey, Ogedegbe, & Agyemang, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…Intrapersonal barriers, including a lack of knowledge, limited English proficiency, and poor prediagnostic medication adherence, may increase cardiovascular risks and result in delayed hospital presentation and diagnosis at an advanced stage of disease. The participants’ poor knowledge of CHD and risk factors is consistent with recent findings from an Australian study inclusive of many cultures (Kilkenny et al, 2017). Lack of knowledge about CHD is known to undermine appropriate self-management of risk factors among immigrants (de-Graft Aikins, Pitchforth, Allotey, Ogedegbe, & Agyemang, 2012).…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, Lynch et al (2006) have found that CVD risk knowledge was high in individuals with CVD risk. In addition, consistent with our results, Kilkenny et al (2017) have found that patients with CVD/CVD risk had inadequate knowledge regarding CVD risks compared with individuals without CVD/CVD risk. Flink et al (2013) have found that individuals with high CVD risk scores had low CVD risk knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, risk knowledge decreased with increasing age. In a study by Kilkenny et al (2017), CVD risk knowledge was assessed in patients with CVD or those with CVD risk and a lower knowledge level was found particular among patient ≥55 years of age. Aging is a complex process involving many physiological changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, too many patients with T2D lack awareness of CV risk factors [112,113], and even those who are aware may not be optimally improving lifestyle factors to manage risk, or sufficiently accessing specialist care [113].…”
Section: Facilitate Patient Empowerment While Helping Patients Undersmentioning
confidence: 99%